Comparison of Optical Scanners for Reverse Engineering Applications on Glossy Freeform Artifact Pharaoh - Koptis, Michal; Resl, Jiri; Urban, Jan; Simota, Jan; Kyncl, Jiri; Mikes, Petr; Beranek, Libor (Manufacturing Technology Journal, 2025)
Article deals with analysis on influence of post-process settings profiles in the Polyworks software and its influence on measuring bias (difference between average surface profile deviation and artifact reference value) and standard deviation of measured data. The comparison was evaluated on glossy artifacts with freeform surfaces. Setting with least bias and standard deviation was than used to evaluate repeatability and systematic measurement error and minimum tolerance bandwidth Tmin according to VDA 5 and MSA 4, respectively for three conceptions of laser scanning technologies available on today's market. Cartesian CMM LK Altera S with laser scanner Nikon LC15Dx (automated technology), Measuring arm Nikon MCAx S30 with laser scanner Nikon H120 (manual technology) and optically tracked handheld device Metronor M-Scan with laser scanner Nikon H120 (manual technology). The conclusions of the study can serve as a guide in technology selection for reverse engineering input data acquisition. Subsequently, the optimal parameters of the post-process settings (for glossy surfaces) in the Polyworks software are listed.
Keywords: Freeform reverse engineering; 3D laser scanners accuracy; Glossy artifact; Measurement capability